A ctab-modified two-dimensional rub-18 zeolite membrane, its preparation method and application in gas separation

The preparation method of CTAB-modified two-dimensional RUB-18 zeolite membrane solves the bottleneck problem of the upper limit of traditional membrane separation, and achieves gas separation effect with high permeability and high selectivity, which is suitable for large-scale industrial production.

CN118236855BActive Publication Date: 2025-12-19SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410358611.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2025-12-19
Estimated Expiration
2044-03-27

AI Technical Summary

Technical Problem

Existing technologies struggle to effectively increase gas permeation while maintaining good gas separation, resulting in a bottleneck limitation on the upper limit of traditional polymer membrane separation.

Method used

A method for preparing a CTAB-modified two-dimensional RUB-18 zeolite membrane includes ball milling to exfoliate two-dimensional RUB-18 zeolite nanosheets and electrophoretic deposition on a porous substrate to form a membrane. The permeability and selectivity are optimized by utilizing the properties of the CTAB-modified nanosheets.

Benefits of technology

It achieves gas separation performance that meets industrial requirements, with significantly improved permeation, good stability, and nanometer-level membrane thickness, making it suitable for industrial needs. In particular, it exhibits high selectivity and good hydrothermal stability in H2/CO2 separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118236855B_ABST
    Figure CN118236855B_ABST
Patent Text Reader

Abstract

The application provides a CTAB modified two-dimensional RUB-18 zeolite membrane and a preparation method and application thereof in gas separation, and belongs to the technical field of two-dimensional nanosheet membrane preparation and gas separation. Two-dimensional RUB-18 zeolite nanosheet solution is obtained by ball milling and peeling; CTAB is doped into the two-dimensional RUB-18 zeolite nanosheet solution; and a porous substrate is put into the two-dimensional RUB-18 zeolite nanosheet solution doped with CTAB, so that a two-dimensional RUB-18 zeolite membrane is prepared by electrophoretic deposition. The method is mild and simple, the two-dimensional RUB-18 zeolite membrane is prepared from the two-dimensional RUB-18 zeolite nanosheet modified by CTAB, is simple, efficient, low in cost, and can grow a two-dimensional RUB-18 zeolite membrane with a thickness of 200-1000 nm on the porous substrate in 5-50 minutes, can be used for gas separation, and can balance permeability and selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of two-dimensional nanosheet membrane preparation and gas separation, and particularly relates to a CTAB modified two-dimensional RUB-18 zeolite membrane and a preparation method and application thereof in gas separation. BACKGROUND

[0002] Hydrogen is one of the most attractive energy carriers, which has the potential to solve energy supply security and environmental problems. Hydrogen is mainly produced by steam reforming of natural gas. However, the by-products CO2 and residual CH4 inevitably coexist in the final gas product. In order to produce high-purity hydrogen and reduce greenhouse gas emissions, hydrogen purification and greenhouse gas capture are particularly important. Separation, as a low-energy and environmentally friendly technology, is expected to replace traditional separation processes such as distillation, adsorption, etc. [J. Wang, Y. Fan, J. Jiang, Z. Wan, S. Pang, Y. Guan, H. Xu, X. He, Y. Ma, A. Huang, P. Wu, Angew. Chem. Int. Ed. 2023, 62, e202304734.] Based on the separation membrane of the new two-dimensional material, because the size / physicochemical properties and interlayer spacing of the assembly unit can be regulated respectively, the permeability and selectivity can be optimized respectively, which is expected to break through the bottleneck limit of the upper limit of traditional polymer membrane separation.

[0003] In the case of maintaining good gas separation, if the gas permeation amount can be further expanded, it will better meet the actual production demand, therefore, it is of great significance to prepare a membrane with both gas separation and gas permeation amount. SUMMARY

[0004] To solve the above technical problems, the application provides a CTAB (cetyltrimethylammonium bromide) modified two-dimensional RUB-18 zeolite membrane and a preparation method and application thereof in gas separation.

[0005] To achieve the above purpose, the application provides the following technical solutions.

[0006] One of the technical solutions of the application is:

[0007] A preparation method of a CTAB modified two-dimensional RUB-18 zeolite membrane, comprising the following steps:

[0008] Ball milling and peeling to obtain a two-dimensional RUB-18 zeolite nanosheet solution;

[0009] CTAB is doped in the two-dimensional RUB-18 zeolite nanosheet solution;

[0010] Put the porous substrate into the two-dimensional RUB-18 zeolite nanosheet solution doped with CTAB to prepare a two-dimensional RUB-18 zeolite film by electrophoretic deposition.

[0011] Further, the method for obtaining the two-dimensional RUB-18 zeolite nanosheet solution by ball milling is as follows:

[0012] Mix the RUB-18 zeolite powder with a mixed solution of methanol and water, and ball mill to obtain a two-dimensional RUB-18 zeolite nanosheet solution.

[0013] Further, the ball milling time is 5-24 h, and the rotation speed is 50-500 rpm.

[0014] Further, the volume ratio of the methanol and water is (0.2-5) : 1.

[0015] Further, the mass-volume ratio of the CTAB and the two-dimensional RUB-18 zeolite nanosheet solution is (0.1-20) mg to (50-300) mL.

[0016] Further, the porous substrate is polyvinylidene fluoride (PVDF), polyether sulfone (PES), sulfonated polysulfone (SPSF), anodic aluminum oxide (AAO), or alpha-alumina, preferably alpha-alumina. Different substrates have an impact on the performance of the film. The above-mentioned substrates selected by the present application are good in flexibility, and the pore size is appropriate and uniform. If the pore size is too large, the nanosheets are prone to collapse when stacking; if the pore size is too small, the gas permeation amount will be affected. The surface of the substrate selected by the present application is flat, reducing defects during film formation. At the same time, considering the cost and scaling problems, the substrate selected by the present application is inexpensive and has better mechanical properties. The surface of the alpha-alumina substrate is more flat, and the pore size is more uniform, so the substrate is preferably alpha-alumina.

[0017] Further, during the electrophoretic deposition, the concentration of the two-dimensional RUB-18 zeolite nanosheet solution of the CTAB is 0.1-10 mg / mL, the voltage is 1-40 V, the current is 0.001-0.010 A, and the time is 5-50 min. The voltage, time, and solution concentration during the electrophoretic deposition all affect the performance of the film. If the voltage is too small, the electric field will be too weak, the nanosheets will move and stack too little, the substrate will not be fully covered, and defects will be generated. If the voltage is too large, the nanosheets will aggregate, and defects will be generated. Under normal circumstances, the longer the time, the more nanosheets will be stacked on the substrate, and the fewer defects will be generated. However, the film thickness will increase, and the gas permeation amount will decrease. If the solution is too dilute, there will be too few nanosheets, and defects will be easily generated. If the solution is too concentrated, the nanosheets will easily aggregate or have thick sheets on the substrate, and defects will be easily generated. Therefore, the present application limits the voltage, time, and solution concentration during the electrophoretic deposition.

[0018] Further, after the electrophoretic deposition is completed, the electrophoretic deposition product is dried to obtain the CTAB-modified two-dimensional RUB-18 zeolite membrane.

[0019] Further, the drying method is not limited, and any drying method that can achieve the drying effect can be used, such as natural ventilation drying, normal temperature vacuum drying, or low temperature vacuum drying, the drying temperature is 25-80℃, and the drying time is 6-48h.

[0020] The application provides a mild method for preparing two-dimensional RUB-18 zeolite nanosheets by ball milling, and the two-dimensional RUB-18 zeolite nanosheets modified by CTAB are simple and efficient in the preparation of two-dimensional RUB-18 zeolite membranes, low in cost, and a layer of two-dimensional RUB-18 zeolite membrane modified by CTAB with a thickness of 200-1000nm can be grown on a porous substrate in 5-50 minutes, and the two-dimensional RUB-18 zeolite membrane modified by CTAB can be successfully used for gas separation, and the permeability and selectivity can be considered.

[0021] The second technical scheme of the application:

[0022] A CTAB-modified two-dimensional RUB-18 zeolite membrane prepared by the preparation method has a thickness of 200-1000nm.

[0023] The third technical scheme of the application:

[0024] The application of the CTAB-modified two-dimensional RUB-18 zeolite membrane in gas separation, wherein the gas is at least one of hydrogen, a gas with different kinetic diameters and characteristics from hydrogen.

[0025] Further, the separated gas is one or two of hydrogen (H2, 0.29nm (diameter, same below)), carbon dioxide (CO2, 0.33nm), nitrogen (N2, 0.36nm), methane (CH4, 0.38nm), ethylene (C2H4, 0.39nm), propylene (C3H6, 0.40nm), ethane (C2H6, 0.42nm) and propane (C3H8, 0.43nm), and especially has high selectivity and good hydrothermal stability for H2 / CO2 separation; when the separated gas is two, the volume ratio of the separated gas is 1:1, and the total flow rate is 20-200mL; the purge gas is one of argon (Ar), helium (He) and methane (CH4), and the total flow rate is 20-100mL.

[0026] Compared with the prior art, the application has the following advantages and technical effects:

[0027] (1) The application utilizes electrophoretic deposition technology to simply prepare the CTAB modified two-dimensional RUB-18 zeolite membrane which reaches the industrial requirements of gas separation performance, the permeation amount is greatly improved compared with the pure RUB-18 zeolite membrane, the stability is also better, and the film thickness of the application is very small, which is nanometer level, the film thickness is only 200-1000 nm, which overcomes the defect that the film of the prior art is micron level thickness, and the film of the application is more suitable for industrial requirements.

[0028] (2) The application first realizes the application of the CTAB modified two-dimensional RUB-18 zeolite membrane in gas separation.

[0029] (3) The application successfully obtains the CTAB modified two-dimensional RUB-18 nanosheet by adding CTAB and stirring and mixing with the original nanosheet.

[0030] (4) The CTAB modified two-dimensional RUB-18 zeolite membrane prepared by the application can exhibit good gas separation selectivity and flux when applied to gas separation, especially H2 / CO2 separation, and has good water vapor and long period stability (>80h), is very suitable for industrialized large-scale production, and has good industrial amplification application potential in the field of gas separation. BRIEF DESCRIPTION OF DRAWINGS

[0031] The accompanying drawings, which form a part of this application, are included to provide a further understanding of the application and are incorporated in and constitute a part of this application. The illustrations, together with their description, serve to explain the application without limiting it.

[0032] Figure 1 It is a scanning electron microscope (SEM) diagram of the CTAB modified two-dimensional RUB-18 zeolite nanosheet of Example 1.

[0033] Figure 2 It is a performance diagram of the CTAB modified two-dimensional RUB-18 zeolite membrane of Example 1 separating different gases. DETAILED DESCRIPTION

[0034] Various illustrative embodiments of the present application are described below in detail. This detailed description is considered one of the best modes for carrying out the application and includes the best modes contemplated for the application. It is to be understood that the application is not limited to the described embodiments and / or modes, but instead, includes all alternatives consistent with the principles and features described herein.

[0035] It should be understood that the terms used herein are merely for the purpose of describing particular embodiments and are not intended to limit the application. In addition, for numerical ranges in the application, it should be understood that each intermediate value between the upper limit and the lower limit of the range is specifically disclosed. Each smaller range within any stated range and any other stated range within the stated range is also included in the application. The upper limit and the lower limit of these smaller ranges can be independently included or excluded from the range.

[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as those commonly understood by one of ordinary skill in the art to which this application pertains. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present application, the preferred methods and materials are described. All publications mentioned in this specification are herein incorporated by reference to disclose and describe the methods and / or materials in connection with which the publications are cited. The citation of any reference is not an admission that it is prior art with respect to the present application.

[0037] Many modifications and variations of this application can be made in the light of the above teachings without departing from the spirit or scope of the application. Other implementations of the application will be apparent to those skilled in the art from consideration of the specification and practice of the application disclosed herein. The specification and examples given are exemplary only.

[0038] As used herein, the terms "comprises", "comprising", "includes", "including", "has", "having", "contains", "containing", or variations thereof, are intended to be open-ended terms that mean including, but not limited to.

[0039] The raw materials used in the embodiments of the present application are all commercially available.

[0040] The technical solutions of the present application are further illustrated by the following examples.

[0041] The preparation method of the RUB-18 zeolite powder in the embodiments of the present application is as follows: raw materials SiO2, NaOH and H2O are weighed according to the mass-volume ratio of 15g:2.2g:10mL respectively, then mixed, magnetically stirred for 2h, transferred into a reaction kettle and reacted at 100℃ for 18 days, then placed in an oven for drying after the reaction is completed, and the RUB-18 zeolite powder is obtained.

[0042] Example 1

[0043] The preparation method of the CTAB modified two-dimensional RUB-18 zeolite membrane in this embodiment is as follows:

[0044] (1) The two-dimensional RUB-18 zeolite nanosheet solution is obtained by taking 30mg of RUB-18 zeolite powder, adding it into a ball mill tank containing 20mL of a mixed solution of methanol and water in a volume ratio of 1:1, and ball milling for 18h at a ball mill speed of 350rpm, thereby obtaining the two-dimensional RUB-18 zeolite nanosheet solution;

[0045] (2) CTAB modified two-dimensional RUB-18 zeolite nanosheet solution: 5 mg of CTAB was added into 150 mL of the two-dimensional RUB-18 zeolite nanosheet solution prepared in step (1) and magnetically stirred at a speed of 30 r / min for 24 h to obtain a CTAB modified two-dimensional RUB-18 zeolite nanosheet solution. The scanning electron microscope (SEM) image of the CTAB modified two-dimensional RUB-18 zeolite nanosheet is shown in FIG. 2. Figure 1 The specific method is to drop the solution containing the zeolite nanosheet on the gold sprayed AAO, and after the solvent is volatilized, the CTAB modified two-dimensional RUB-18 zeolite nanosheet with a square-like intermediate part is observed under the electron microscope. Figure 1 The specific method is to drop the solution containing the zeolite nanosheet on the gold sprayed AAO, and after the solvent is volatilized, the CTAB modified two-dimensional RUB-18 zeolite nanosheet with a square-like intermediate part is observed under the electron microscope. Figure 1 It can be seen from FIG. 2 that the morphology of the modified nanosheet is not damaged.

[0046] (3) The α-alumina was put into the CTAB modified two-dimensional RUB-18 zeolite nanosheet solution with a concentration of 8 mg / mL as a porous substrate, and electrophoretic deposition was performed at a voltage of 20 V, a current of 0.002 A and a time of 20 min.

[0047] (4) The electrophoretic deposition product of step (3) was dried by low-temperature vacuum drying at a temperature of 60°C for 12 h to obtain a CTAB modified two-dimensional RUB-18 zeolite film.

[0048] The CTAB modified two-dimensional RUB-18 zeolite film prepared in this example was used for gas separation.

[0049] The prepared CTAB modified two-dimensional RUB-18 zeolite film was assembled into a gas mold for gas separation test (the same below), and the specific method was as follows: the dried two-dimensional RUB-18 zeolite film was placed in the mold, the single gas or mixed gas to be tested was introduced into the upper part of the mold, the purge gas was introduced into the lower part of the mold to drive the gas to continuously pass through the film, and the other part was introduced into the chromatograph to observe the results. The types of raw gas were hydrogen (H2, 0.29 nm) and carbon dioxide (CO2, 0.33 nm), hydrogen (H2, 0.29 nm) and nitrogen (N2, 0.36 nm), hydrogen (H2, 0.29 nm) and methane (CH4, 0.38 nm), and hydrogen (H2, 0.29 nm) and propylene (C3H6, 0.40 nm). The volume ratio of the gas was 1:1, and the total flow rate was 50 mL. The purge gas was argon (Ar), and the total flow rate was 25 mL. The gas separation performance was detected by Agilent gas chromatograph 7890A and calculated.

[0050] The gas flux in the experimental test parameters is represented by P, and the unit is GPU, 1 GPU = 3.35 x 10 -10 mol·m -2·s -1 ·pa -1 , the gas fluxes are P(H2) = 1825 GPU, P(CO2) = 17 GPU, P(N2) = 22 GPU, P(CH4) = 20 GPU, and P(C3H6) = 10 GPU, respectively, and the corresponding gas selectivities of H2 / CO2, H2 / N2, H2 / CH4, and H2 / C3H6 are 10783 91, 183, respectively. The experimental results of the gas fluxes are shown in Table 1. Figure 2

[0051] Example 2

[0052] The preparation method of the CTAB-modified two-dimensional RUB-18 zeolite membrane in this example is as follows:

[0053] (1) The two-dimensional RUB-18 zeolite nanosheet solution was obtained by peeling: 50 mg of the RUB-18 zeolite powder synthesized in step (1) was added to a ball mill tank containing 20 mL of a mixed solution of methanol and water in a volume ratio of 5:1 for ball milling, the ball milling time was 5 h, and the ball mill speed was 500 rpm, thereby obtaining the two-dimensional RUB-18 zeolite nanosheet solution;

[0054] (2) The CTAB-modified two-dimensional RUB-18 zeolite nanosheet solution: 7 mg of CTAB was added to 100 mL of the two-dimensional RUB-18 zeolite nanosheet solution prepared in step (1) and magnetically stirred at a speed of 30 r / min for 24 h to uniformly mix the two;

[0055] (3) The PVDF was placed into the CTAB-modified two-dimensional RUB-18 zeolite nanosheet solution with a concentration of 10 mg / mL for electrophoretic deposition at a voltage of 40 V and a current of 0.001 A for 5 min.

[0056] (4) The electrophoretically deposited product of step (3) was dried by vacuum drying at room temperature for 48 h at a temperature of 25°C to obtain the CTAB-modified two-dimensional RUB-18 zeolite membrane.

[0057] The CTAB-modified two-dimensional RUB-18 zeolite membrane prepared in this example was used for gas separation:

[0058] The raw gas was hydrogen (H2) and carbon dioxide (CO2), the total flow rate of the raw gas was 50 mL, and the volume ratio was 1:1; the sweeping gas was argon (Ar), and the total flow rate was 25 mL. The gas separation performance was calculated after detection by Agilent gas chromatograph 7890A.

[0059] ​The gas fluxes tested in the experiment were P(H2) = 2121 GPU and P(CO2) = 106 GPU, and the H2 / CO2 gas selectivity was 20.

[0060] Example 3

[0061] The preparation method of the CTAB-modified two-dimensional RUB-18 zeolite membrane in this example is as follows:

[0062] (1) The two-dimensional RUB-18 zeolite nanosheet solution was obtained by peeling: 5 mg of RUB-18 zeolite powder was taken and added to a ball mill tank containing 20 mL of a mixed solution of methanol and water in a volume ratio of 1:5 for ball milling, the ball milling time was 24 h, and the ball mill speed was 50 rpm, thereby obtaining a two-dimensional RUB-18 zeolite nanosheet solution;

[0063] (2) The CTAB-modified two-dimensional RUB-18 zeolite nanosheet solution: 5 mg of CTAB was weighed and added to 125 mL of the nanosheet solution prepared in step (1), and magnetic stirring was performed at a stirring speed of 30 r / min for 24 h to uniformly mix the two;

[0064] (3) The AAO was placed as a porous substrate into the RUB-18 zeolite nanosheet solution with a concentration of 0.1 mg / mL, and electrophoretic deposition was performed at a voltage of 1 V and a current of 0.01 A for 50 min;

[0065] (4) The electrophoretically deposited product of step (3) was dried by natural ventilation, the drying temperature was 25°C, and the drying time was 24 h, thereby obtaining a CTAB-modified two-dimensional RUB-18 zeolite membrane.

[0066] Application of the CTAB-modified two-dimensional RUB-18 zeolite membrane prepared in this example in gas separation:

[0067] The raw gas was hydrogen (H2) and carbon dioxide (CO2), the total flow rate of the raw gas was 50 mL, and the volume ratio was 1:1; the purge gas was argon (Ar), and the total flow rate was 25 mL. The gas separation performance was detected by Agilent gas chromatograph 7890A and calculated.

[0068] The gas fluxes tested in the experiment were P(H2) = 2121 GPU and P(CO2) = 106 GPU, and the H2 / CO2 gas selectivity was 20.

[0069] Example 4

[0070] The preparation method of the CTAB-modified two-dimensional RUB-18 zeolite membrane in this example is as follows:

[0071] (1) Two-dimensional RUB-18 zeolite nanosheet solution was obtained by peeling: 30 mg of RUB-18 zeolite powder was added to a ball mill tank containing 20 mL of a mixed solution of methanol and water in a volume ratio of 1:1 for ball milling, the ball milling time was 15 h, and the ball mill speed was 200 rpm, thereby obtaining a two-dimensional RUB-18 zeolite nanosheet solution;

[0072] (2) CTAB-modified two-dimensional RUB-18 zeolite nanosheet solution: 5 mg of CTAB was added to 75 mL of the nanosheet solution prepared in step (1) and magnetically stirred at a speed of 30 r / min for 24 h to uniformly mix the two;

[0073] (3) PES was placed as a porous substrate into a two-dimensional RUB-18 zeolite nanosheet solution with a concentration of 8 mg / mL, and electrophoretic deposition was performed at a voltage of 30 V and a current of 0.005 A for 20 min;

[0074] (4) The electrophoretically deposited product of step (3) was dried by low-temperature vacuum drying at a temperature of 50°C for 18 h to obtain a CTAB-modified two-dimensional RUB-18 zeolite membrane.

[0075] The CTAB-modified two-dimensional RUB-18 zeolite membrane prepared in this example was used for gas separation:

[0076] The raw gas was hydrogen (H2) and carbon dioxide (CO2), and the total flow rate of the raw gas was 50 mL with a volume ratio of 1:1; the purge gas was argon (Ar) with a total flow rate of 25 mL. The gas separation performance was calculated after detection by Agilent gas chromatograph 7890A.

[0077] The gas fluxes tested in the experiment were P(H2) = 2120 GPU and P(CO2) = 106 GPU, and the H2 / CO2 gas selectivity was 20.

[0078] Example 5

[0079] The preparation method of the CTAB-modified two-dimensional RUB-18 zeolite membrane in this example is as follows:

[0080] (1) Two-dimensional RUB-18 zeolite nanosheet solution was obtained by peeling: 30 mg of RUB-18 zeolite powder was added to a ball mill tank containing 20 mL of a mixed solution of methanol and water in a volume ratio of 1:1 for ball milling, the ball milling time was 15 h, and the ball mill speed was 200 rpm, thereby obtaining a two-dimensional RUB-18 zeolite nanosheet solution;

[0081] (2) CTAB modified two-dimensional RUB-18 zeolite nanosheet solution: 5 mg of CTAB was added into 200 mL of the nanosheet solution prepared in step (1) and magnetically stirred at a speed of 30 r / min for 24 h to uniformly mix the two;

[0082] (3) The SPSF was placed into the RUB-18 zeolite nanosheet solution with a concentration of 8 mg / mL and electrophoretically deposited at a voltage of 10 V and a current of 0.008 A for 25 min;

[0083] (4) The electrophoretically deposited product of step (3) was dried by low-temperature vacuum drying at a temperature of 40 °C for 40 h to obtain a CTAB modified two-dimensional RUB-18 zeolite membrane.

[0084] The CTAB modified two-dimensional RUB-18 zeolite membrane prepared in this example was used for gas separation:

[0085] The raw gas was hydrogen (H2) and carbon dioxide (CO2) with a total flow rate of 50 mL and a volume ratio of 1:1, and the purge gas was argon (Ar) with a total flow rate of 25 mL. The gas separation performance was calculated after detection by Agilent gas chromatograph 7890A.

[0086] The gas fluxes tested in the experiment were P(H2) = 885 GPU and P(CO2) = 8.7 GPU, and the H2 / CO2 gas selectivity was 101.

[0087] Comparative Example 1

[0088] The same as Example 1, except that CTAB was replaced by tetramethylammonium hydroxide.

[0089] The same test method as in Example 1 was used, and the gas fluxes tested in the experiment were P(H2) = 625 GPU and P(CO2) = 42.5 GPU, and the H2 / CO2 gas selectivity was 32.

[0090] Since the modifier in this comparative example is a short chain, the interlayer does not increase significantly, the gas permeation amount does not increase significantly, and the binding ability between the modified nanosheets is also poor, and the performance also decreases significantly.

[0091] Comparative Example 2

[0092] The same as Example 1, except that CTAB was not used to modify the two-dimensional RUB-18 zeolite nanosheet solution, i.e., step (2) was not performed.

[0093] Using the same test method as in Example 1, the gas fluxes are P(H2) = 420 GPU, P(CO2) = 1.9 GPU, P(N2) = 1.8 GPU, P(CH4) = 1.6 GPU, P(C3H6) = 0.9 GPU, and the corresponding gas selectivities of H2 / CO2, H2 / N2, H2 / CH4, H2 / C3H6 are 221, 233, 263, 467, respectively.

[0094] From Example 1 and Comparative Example 2, it can be seen that the hydrogen permeation amount of the RUB-18 zeolite membrane modified by CTAB is 4 times that of the RUB-18 zeolite membrane not modified by CTAB, although the selectivity has decreased to some extent, but the amount of gas processed per day in industry is large, and high permeation amount is more suitable for industrial processing.

[0095] The above merely describes the preferred embodiments of the present application, but the scope of protection of the present application is not limited thereto, and any person skilled in the art can easily think of changes or replacements within the technical scope disclosed by the present application, which should be covered within the scope of protection of the present application. Therefore, the scope of protection of the present application should be subject to the scope of protection of the claims.

Claims

1. Use of a CTAB-modified two-dimensional RUB-18 zeolite membrane in gas separation, characterized in that, The gas is at least one of hydrogen, a gas with a different kinetic diameter and characteristics from hydrogen; The method for preparing the CTAB-modified two-dimensional RUB-18 zeolite film comprises the following steps: Ball milling to obtain a two-dimensional RUB-18 zeolite nanosheet solution; CTAB is doped into the two-dimensional RUB-18 zeolite nanosheet solution; A porous substrate is placed into the two-dimensional RUB-18 zeolite nanosheet solution doped with CTAB to prepare a two-dimensional RUB-18 zeolite film by electrophoretic deposition; The method for ball milling to obtain a two-dimensional RUB-18 zeolite nanosheet solution is as follows: RUB-18 zeolite powder is mixed with a mixed solution of methanol and water, and ball milling is performed to obtain a two-dimensional RUB-18 zeolite nanosheet solution; During electrophoretic deposition, the concentration of the two-dimensional RUB-18 zeolite nanosheet solution with CTAB is 0.1-10 mg / mL, the voltage is 1-40 V, the current is 0.001-0.010 A, and the time is 5-50 min; The thickness of the CTAB-modified two-dimensional RUB-18 zeolite film is 200-1000 nm.

2. Use according to claim 1, characterized in that, The ball milling time is 5-24 h, and the rotation speed is 50-500 rpm.

3. Use according to claim 1, characterized in that, The volume ratio of methanol to water is (0.2-5):

1.

4. Use according to claim 1, characterized in that, The mass-to-volume ratio of CTAB to the two-dimensional RUB-18 zeolite nanosheet solution is (0.1-20) mg:(50-300) mL.

5. The use according to claim 1, characterized in that, After electrophoretic deposition, the electrophoretic deposition product is dried to obtain a CTAB-modified two-dimensional RUB-18 zeolite film.

6. Use according to claim 1, characterized in that, The type of separated gas is one or two of hydrogen, carbon dioxide, nitrogen, methane, ethylene, propylene, ethane and propane; When the separated gas is two, the volume ratio of the separated gas is 1:1; and the purge gas is one of argon, helium and methane.

Citation Information

Patent Citations

  • Preparation method of functionalized two-dimensional nano-material and functionalized nano thin film

    CN108455541A

  • Two-dimensional layered zeolite molecular sieve membrane with high separation stability as well as preparation method and application thereof

    CN112279264A

  • Method for rapidly preparing two-dimensional zeolite molecular sieve membrane by electrophoretic deposition and two-dimensional zeolite molecular sieve membrane prepared by method

    CN112705056A